LANDASAN FILOSOFIS PENDIDIKAN: Telaah Pemikiran Socrates, Plato dan Aristoteles - Tang, Muhammad; Mansur, A.H; Ismail, Ismail (Asosiasi Dosen PTKIS Indonesia, 2021)
Abstract: The orientation of education in Indonesia is more likely to lead to the foundation that has been built by Western philosophers from three well-known philosopher figures, namely Socrates, Plato, and Aristotle. The purpose of this paper is to reveal the educational thoughts of these three philosopher figures so that they can become the foundation of educational philosophies that are developing today. The research method used is a qualitative analytical-descriptive method by examining the thoughts of the three philosopher figures and being compared by looking at the phenomena of today's society. Based on the research results in this paper, it shows that the philosophical foundation of education that can be adapted from the thoughts of Socrates, Plato and Aristotle at this time, namely; education is carried out in a dialogical manner, critical thinking, the need for the participation of the government and society, education is directed to conquer passions by reason, the purpose of education is to achieve speculative happiness. These philosophical foundations need to be built in today's education.